Activation and Regulation of Cellular Eicosanoid Biosynthesis - Thomas G. Brock; Marc Peters-Golden (The Scientific World Journal)
There is a growing appreciation for the wide variety of physiological responses that are regulated by lipid messengers. One particular group of lipid messengers, the eicosanoids, plays a central role in regulating immune and inflammatory responses in a receptor-mediated fashion. These mediators are related in that they are all derived from one polyunsaturated fatty acid, arachidonic acid. However, the various eicosanoids are synthesized by a wide variety of cell types by distinct enzymatic pathways, and have diverse roles in immunity and inflammation. In this review, the major pathways involved in the synthesis of eicosanoids, as well as key points of regulation, are presented.